Prevention and treatment of behavioural and learning disorders with sensory integration therapy - Reményi, Tamás (Gyermeknevelés Tudományos Folyóirat, 2022)
Sensory integration disorders, which are often hidden in the background of learning and/or behavioural disorders, can cause serious difficulties in the daily activities of the students, in the implementation of learning and/or behaviour. Upon hearing the term ‘sensory integration’, two interpretations appear in the minds of professionals. On interpretation refers to the integration, sensory interconnection coordination and interdependence of sensory systems as a typical, neurological maturation process that provides the basis for subsequent learning and behavioural organisation processes. Based on a second interpretation, ‘sensory integration’ is a therapeutic methodology, diagnostic, and therapeutic procedure that provides assistance to people who are lagging behind in the maturation of sensing systems and perception processes. Learning and/ or behavioural disorders can be caused by impaired information acquisition processes, sensory modulation, and integration in the nervous system. The following study comprehensively presents the diagnostic process and the relationship between the learning and behavioural differences related to sensory integration disorders.